Yogyakarta netizen community response to the black campaign: the 2014 presidential election in Indonesia - Pratama Dahlian Persadha; Irwan Abdullah; S. Bayu Wahyono (Department of Communications, Universitas Islam Indonesia, 2017)
This research examines the netizen communities’ reception of the 'black' campaigning before the Indonesian Presidential Election of 2014, especially focuses on how the general public gave meaning to the black campaigns presented textually through online mass media (specifically okezone.com and detik.com) in the run-up to the Indonesian Presidential Election. The findings state that netizen communities' reception to the black campaigning in the lead-up to the election was not homogenous, but rather depended greatly on background factors such as political ideology, social status, cultural background, past experiences, and family characters. Public belief in the content of the black campaigns also varied; some believed the negative rumors being spread, whereas others did not believe these rumors at all. It is obvious that the black campaigning through the new media generally did not influence netizen communities' perceptions, but rather reinforced their own political preferences that had already divided them into groups supporting specific candidates. In receiving the messages and rumors spread by black campaigns through online mass media, netizens did not act as individuals, but rather as collectives united by specific political ideologies and socio-cultural values which were socialized through family institutions. Keywords: 'black' campaigns; netizens; public reception; online media; Yogyakarta